Salivary retention after application of fluoride gel using toothbrush or tray: a crossover trial - Cecilia Claudia Costa Ribeiro; Estevam Carlos de Oliveira Lula; Izabelle Maria Cabral de Azevedo; Mariana de Figueiredo Lopes e Maia; Fernanda Ferreira Lopes (Sociedade Brasileira de Pesquisa Odontológica, 2012)
Currently, there are no studies in the literature evaluating salivary fluoride retention after small amounts of fluoride gel are applied to children's teeth. Therefore, the objective of the present study was to compare salivary retention after gel application using a toothbrush or by traditional application with trays. In this crossover study, children with active caries (n = 10) were randomized into one of the following treatment groups: a) application of fluoride gel using a tray (control), or b) application of fluoride gel with a toothbrush (treatment). After a 7-day washout period, the treatments were inverted. Unstimulated saliva samples were collected at baseline and 0.5, 5, 15, 30, 60 and 120 minutes after acidulated phosphate fluoride (APF) gel application in order to analyze fluoride retention in saliva. The area under the curve (AUC) was also calculated. There were no differences in fluoride retention after application of small amounts of APF with a toothbrush compared to traditional gel application using trays at all time points studied, and no differences in AUC were observed (Student t-test, p > 0.05). These results suggest that application of fluoride gel in children using a toothbrush can be utilized as an option rather than traditional trays, since the same salivary retention of fluoride is obtained using a lower dose.